Abstracts of Philippine researches in guidance 1971-1976 - Agustin, Leila M. (1977)
This special problem aims to provide guidance workers and researchers with a listing of abstract of researches on guidance done from 1971 to 1976. It continues "Ten Years of Philippine Researches in Guidance, 1961-1970" by the Philippine Guidance and Personnel Association (PGPA) and "Abstracts of Philippine Researches in Guidance, 1951-1960" by Estella Antonio. Bibliographical catalogs and lists of various libraries in Metro Manila were utilized in compiling and locating theses and dissertations. Periodical indexes were used for gathering titles of researches published in local journals. In addition, card catalogs of different libraries were also consulted. Reports on original researches were found in fifteen institutional libraries in Manila.